Methods of Forecasting Credit Losses in A Sample of Iraqi Banks - A Comparative Analysis - DHEYAA JASIM, RABEAH; N. Abdullah Al-Mashhdani, Bushra (Journal of Economics and Administrative Sciences, 2022)
The general trend in Iraqi banks is focused towards the application of international financial reporting standards, especially the international financial reporting standard IFRS 9 “Financial Instruments”, in addition to the directives issued on the Central Bank of Iraq’s instructions for the year 2018 regarding the development of expected credit losses models, and not to adhere to a specific method for calculating these losses and authorizing the banks’ departments to adopt the method of calculating losses that suits the nature of the bank’s activity and to be consistent in its use from time to time. The research problem revolves around the different methodologies for calculating expected credit losses according to the instructions of the Central Bank of Iraq compared to the requirements for calculating those losses according to IFRS 9, as well as the difference between the banks listed in the Iraq Stock Exchange among themselves. The research aims to present methods of forecasting expected credit losses in a sample of Iraqi banks and compare them with the requirements of IFRS 9 and the instructions of the Central Bank of Iraq in this regard. The research reaches a set of conclusions, the most important of which is that the International Financial Reporting Standard IFRS 9 has not been fully applied in Iraqi banks so far. There is also a difference between banks in the methods of calculating expected credit losses according to the mentioned criterion. And based on the conclusions that come, the research presents a set of recommendations, the most important of which is the necessity of preparing the infrastructure in the Iraqi environment first so that the standard can be applied correctly by subjecting the employees to training courses to familiarize them with the IFRS 9 standard, its application methods and requirements.